Protecting consumers from misleading online advertisement for herbal and traditional medicines in Malaysia: are the laws sufficient? - Ismail, Suzi Fadhilah; Daud, Mahyuddin; Abd. Jalil, Juriah; Abdul Ghani Azmi, Ida Madieha; Safuan, Sahida (IEEE Xplore, 2019)
Herbal supplements and traditional medicines have become very popular among consumers as part of treatment for diseases as well as to improve general health and well-being. Manufacturers and producers of these products are now taking the benefits of the internet to market them as they could easily reach a large number of potential buyers and end-users. In fact, internet advertising has globally become one of the favourite models of advertising with the rise of digital equipment and media in particular smart phones and other gadgets which enable access to the internet. The problem arises when some online advertisements including those published on social media are found to be illegal, misleading and deceptive as it contains inter alia, dubious or unproven claims in relation to the use and efficacy of herbal and traditional medicines. From regulatory perspective, all type of dissemination of information about products and health services including to market the products online are classified as advertisement. In Malaysia, the approval from Medicine Advertisements Board (MAB) under the Ministry of Health (MOH) is required before the advertisement can be published to the public. This paper uses doctrinal legal research method in examining the current issues and challenges revolving around illegal and misleading advertisements of herbal and traditional medicines. It then proceeds to discuss the relevant regulatory framework to address those issues, in particular the important role played by MAB. Relevant legislations from Australia, United States (US) and European Union (EU) are also explored for the purpose of emulating best practices with a view to enhance the existing legal mechanism in Malaysia. The paper concludes with some suggestions to further tighten up some of the provisions in particular the enforcement and monitoring mechanism so that consumers will be better protected from unscrupulous and irresponsible online advertisements.